2019
DOI: 10.1055/a-0828-9831
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Prenylated Xanthones from the Leaves of Garcinia bracteata

Abstract: Six new prenylated xanthones (1–6) and seventeen known xanthones were isolated from extracts of Garcinia bracteata leaves. Their structures were determined by extensive NMR and MS spectroscopic data analysis. The inhibitory activities of the isolates were assayed on HeLa, A549, PC-3, HT-29, and WPMY-1 cell lines. Compounds 1 and 15–17 showed moderate inhibitory effects on tumor cell growth, with IC50s ranging from 3.7 to 14.7 µM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…The 1 H NMR and 13 C NMR data are similar with literature(Zhang et al, 2019).Brasixanthone B (8): yellow needle crystal.…”
supporting
confidence: 82%
“…The 1 H NMR and 13 C NMR data are similar with literature(Zhang et al, 2019).Brasixanthone B (8): yellow needle crystal.…”
supporting
confidence: 82%
“…The common example of Oglycoside xanthone is rutinosylxanthone, while the example of C-glycoside xanthone is mangiferin, as shown in Figure 2. The prenylated xanthone group is characterized by the presence of prenyl and geranyl substituents [32]. The prenylated xanthone group contains the largest number of natural xanthone derivatives, such as α-mangostin, caloxanthone, and calozeylxanthone, as shown in Figure 2.…”
Section: Xanthone Derivativesmentioning
confidence: 99%
“…8-deoxygartanin 2 has been reported in other species of the Clusiaceae family and has been found to have anticancer, anti-Alzheimer’s properties, and the ability to inhibit the PL and AG enzymes [ 34 , 39 , 40 ]. Gartanin 3 has been reported to be found in other species of the Clusiaceae family and multiple studies have shown its anticancer and antitumor properties, and ability to inhibit enzymes such as PL and AA [ 34 , 41 , 42 ]. α-mangostin 4 and γ-mangostin 5 have been isolated from species of the Clusiaceae and Hypericaceae families, and are characterized by their anti-Alzheimer’s, anticancer, anti-inflammatory, anti-diabetic and antiobesity properties [ 26 , 41 , 43 , 44 , 45 , 46 , 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%